2012
DOI: 10.1182/blood-2011-10-385781
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of monosomal karyotype in comparison to complex aberrant karyotype in acute myeloid leukemia: a study on 824 cases with aberrant karyotype

Abstract: In acute myeloid leukemia (AML) the subset with complex karyotype (CK) is traditionally regarded as the worst prognostic group. However, > 3, > 4, or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 12 publications
7
54
2
Order By: Relevance
“…Initially, we determined the frequency and baseline character of MK in Chinese AML patients. In our study, the incidences of monosomy karyotype were 13% in patients age 15 to 60 years and 18% in patients between 15 and 88 years old, which were obviously lower than those reported by Breems et al (25.1% in patients age 15 to 60 years) (Breems et al, 2008), SWOG (28.5% in patients between 16 and 88 years old) (Medeiros et al, 2010), Kayser et al (2012) (30% in patients age 16 to 85 years), and other investigators (Grimwade et al, 2010;Haferlach et al, 2012). This discrepancy might be attributed to two main factors: (1) Compared with many currently published studies on MK, most of which were from large multicenter clinical trials, the present study was from large singlecenter.…”
Section: Discussioncontrasting
confidence: 73%
“…Initially, we determined the frequency and baseline character of MK in Chinese AML patients. In our study, the incidences of monosomy karyotype were 13% in patients age 15 to 60 years and 18% in patients between 15 and 88 years old, which were obviously lower than those reported by Breems et al (25.1% in patients age 15 to 60 years) (Breems et al, 2008), SWOG (28.5% in patients between 16 and 88 years old) (Medeiros et al, 2010), Kayser et al (2012) (30% in patients age 16 to 85 years), and other investigators (Grimwade et al, 2010;Haferlach et al, 2012). This discrepancy might be attributed to two main factors: (1) Compared with many currently published studies on MK, most of which were from large multicenter clinical trials, the present study was from large singlecenter.…”
Section: Discussioncontrasting
confidence: 73%
“…Other karyotypic features such as a structurally complex or monosomal karyotype have been reported as a strong negative prognostic indicator in overall MDS and AML. 10,[25][26][27]36,37 We found that these were also independent indicators of poor prognosis inv(3)/t(3;3) MDS and AML. Interestingly, t(9;22) was noted in 2 inv(3)/t(3;3) AML patients as secondary clonal evolution or part of complex karyotype in a de novo AML patient without history of CML.…”
Section: Discussionmentioning
confidence: 74%
“…1,22 Monosomy 7, in particular, is reported in approximately 40-60% of inv(3)/t(3;3) AML patients and is associated with dismal prognosis. 2,6,22,37 In our series, -7/del(7q) abnormality (37.3%) was the most common additional abnormality and while this was a poor prognostic factor on univariable analysis, it did not retain statistical significance in the multivariable model. Other karyotypic features such as a structurally complex or monosomal karyotype have been reported as a strong negative prognostic indicator in overall MDS and AML.…”
Section: Discussionmentioning
confidence: 86%
“…This category is defined as the presence of two or more autosomal monosomies or one autosomal monosomy in combination with at least one structural chromosomal abnormality. This new risk category is associated with a very poor outcome with an estimated 4-year survival rate of 4% [7,8]. The benefit of SCT in this subpopulation has been studied in several retrospective studies and all of them seem to favor the performance of SCT in CR1 [9]2 [11].…”
Section: Introductionmentioning
confidence: 99%